COVID‐19 vaccination timing and kidney transplant waitlist management: An international perspective. Issue 1 (28th December 2021) - Caliskan, Yasar; Axelrod, David; Guenette, Alexis; Lam, Ngan N.; Kute, Vivek; Alhamad, Tarek; Schnitzler, Mark A.; Lentine, Krista L.
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has created unprecedented challenges for solid organ transplant programs worldwide. The aim of this study is to assess an international perspective on challenges faced by kidney transplant programs. Methods: We administered an electronic survey instrument from January 3, 2021 to June 8, 2021 to staff at transplant programs outside the United States that comprised of 10 questions addressing the management of kidney transplant candidates with asymptomatic COVID‐19 infection or unvaccinated who receive an organ offer. Results: Respondents ( n = 62) represented 19 countries in five continents. Overall, 90.3% of respondents encourage vaccination on the waiting list and prior to planned living donor transplant. Twelve percent of respondents reported that they have decided to inactivate unsensitized candidates (calculated panel reactive antibody, cPRA <80%) until they received the two doses of vaccination, and 7% report inactivating candidates who have received their first vaccine dose pending receipt of their second dose. The majority (88.5%) of international respondents declined organs for asymptomatic, nucleic acid testing (NAT)+ patients during admission without documented prior infection. However, 22.9% of international respondents proceeded with kidney transplant in NAT+ patients who were at least 30 days from initial diagnosis with negative chest imaging. Conclusions: Practitioners in some countries are less willing to accept deceased donor organs for waitlist candidates with incomplete COVID‐19 vaccination status and to wait longer before scheduling living donor transplant, compared to United States practices. Access to vaccinations and other resources may contribute to these differences. More research is needed to guide the optimal approach to vaccination before and after transplant.